Efeito anti-inflamatório do ácido cafeico sobre o sistema purinérgico e colinérgico em ratos Diabéticos tipo 1 - Castro, Milagros Fanny Vera (2020)
Diabetes mellitus (DM) is a metabolic disorder, considered one of the biggest public health problems in the world. This disease is characterized by a state of chronic hyperglycemia that leads to metabolic disorders. Studies have shown changes in lymphocyte functions in diabetic patients and a close relationship with inflammation and a greater likelihood of the development of vascular diseases. Related to this condition, it is known that the purinergic and cholinergic signaling pathways regulate several physiological processes, acting on immune and inflammatory responses. In order to control these inflammatory processes, as well as decrease the incidence of cardiovascular diseases in DM, therapies with natural phenolic substances have been focus of studies. Among these, caffeic acid (CA), besides having anti-inflammatory and antioxidant properties, has been shown to regulate the activity of purinergic enzymes. Thus, the objective of this study was to evaluate the effect of CA on the activity of the enzymes ectonucleoside triphosphate diphosphohydrolase (E-NTPDase) and adenosine deaminase (ADA), on the levels of ATP and on the expression of the A2A receptor at the level of purinergic system, as well as the activity acetylcholinesterase (AChE), butyrylcholinesterase (BuChE) and 7nChR receptor expression at the level of the cholinergic system. In addition, to evaluate the effect of this phenolic compound on the expression of inflammatory cytokines IL-1β, IL-6 and IL-10, on the activity of myeloperoxidase (MPO), as well as on other oxidative parameters in streptozotocin-induced diabetic rats (STZ) 55 mg/kg via intraperitoneal, (those animals that presented blood glucose >250mg/dL were considered diabetic). Male Wistar rats were divided into six groups (n=10): control/oil; control/CA 10 mg/kg; control/CA 50 mg/kg; diabetic/oil; diabetic/CA 10 mg/kg and diabetic/CA 50 mg/kg, treated on the 5th day after induction, for thirty days by oral gavage. On the 31st day, after treatment with CA, the animals were euthanized by exsanguination. Results demonstrated a significant reduction in ATP and ADP hydrolysis in lymphocytes, a reduction in ATP levels in serum, in addition to a decrease in the increase of ADA and AChE activity in lymphocytes, BuChE in serum and MPO in plasma in CA-treated diabetic rats compared with untreated diabetics. In turn, treatment with CA was not able to attenuate the increase in the expression of IL-1β, IL-6 genes in lymphocytes in the diabetic state. However, CA was able to increase the gene expression of IL-10 and A2A receptor regardless of the animals' condition (healthy or diabetic). CA also increased the expression of the α7nAChR receptor in lymphocytes. Additionally, CA attenuated the increase in reactive species (RS) production (plasma), lipid peroxidation and protein oxidation (serum) in diabetic rats when compared to untreated diabetic animals. This phenolic acid also reversed the decrease in plasma levels of total thiols (T-SH) and non-protein thiols (NPSH). Thus, the results obtained indicate that CA was able to modulate the activity of E-NTPDase, ADA, AChE, BuChE and MPO, in addition to increasing anti-inflammatory parameters (IL-10) and reverse the increase of oxidative stress in diabetic state. We can indicate that this phenolic compound attenuates oxidative and inflammatory changes, through the return of homeostasis in the purinergic and cholinergic systems promoted by hyperglycemia in the diabetic state.